Low sleep quality and morningness-eveningness scale score may impair ball placement but not kicking velocity in youth academy soccer players - Palucci Vieira, L. H.; Lastella, M.; da Silva, J. P.; Cesário, T.; Santinelli, F. B.; Moretto, G. F.; Santiago, P. R. P.; Barbieri, F. A. (Science and Medicine in Football, 2022)
Purpose: The current study examined the possible relationships between one-off single night sleep metrics and subsequent kicking performance in a youth soccer context. Methods: Twenty-eight under-17 academy players (15.9±0.8years-old) completed a kick testing protocol consisting in 20 attempts, 18 m from the goal and against a goalkeeper. Four digital video cameras (240Hz) allowed to determine 3-D approach run, lower limb and ball velocities. Two additional cameras (60Hz) were used to calculate 2-D mean radial error, bivariate variable error and accuracy. Over 24h prior to testing, players were monitored by wrist actigraphy to determine their sleep indices. Self-reported sleep quality, sleepiness and chronotype scale scores (Horne and Östberg morningness-eveningness questionnaire) were also collected immediately before kicking experiment. Results: Multiple linear regressions indicated that wake up time and chronotype contributed to 40% of mean radial error. Self-reported sleep quality influenced respectively on 19% and 24% of accuracy and bivariate variable error variances. Taken together self-reported sleep quality and wake up time explained 33% of accuracy (all p <0.05). Indicators of kicking velocity were non-significantly correlated with sleep (r =-0.30-0.29; p >0.05). Conclusion: One-off sleep measures showed some sensitivity to acutely detect inter-individual oscillations in kicking performance. Low perceived sleep quality, later wake up time and a chronotype toward evening preference seem either related to immediately subsequent worst ability of ball placement when kicking. Monitoring sleep-wake transition and perceived sleep quality may be important to help prevent acute performance declines in targeting the goal during kick attempts from the edge of penalty area.